Frequency and antimicrobial behaviour of thermophilic Campylobacter species isolated from ecuadorian backyard chickens - Simaluiza Masabanda, R. (2016)
The prevalence and antimicrobial behaviour of Campylobacter jejuni/coli isolated from backyard chickens from Southern Ecuador were determined. This study revealed that Campylobacter sp. frequency was 41.7% with high resistance to tetracycline (94.0%) and ciprofloxacin (88%). C. jejuni was the most frequently isolated species (32.5%), followed by C. coli (9.2%) being poultry colonization by Campylobacter not region dependent. This is the first study on Campylobacter antimicrobial resistance in backyard chickens in Southern Ecuador.